Case studies for instructional purposes in educational administration - Regis, Paz S. 1932-
Case No.1, "A Principal's Quandary", portrays the ecological factors impinging on disciplinary action against a habitually absent teacher. Case No.2, "The Dilemma of a Classroom Teacher", tells of conflict regarding confidentiality of information from a student. Case No.3 "The University Student Paper", recounts a conflict between administration and the student body concerning student press freedom.